Generation of a High-Affinity Nanobody Against CD147 for Tumor Targeting and Therapeutic Efficacy Through Conjugating Doxorubicin - Li, Rifei; Zhu, Xinjie; Zhou, Peng; Qiao, Yuehua; Li, Yinqian; Xu, Yice; Shi, Xi (Frontiers in Immunology, 2022)
CD147, a glycosylated transmembrane protein in the immunoglobulin superfamily, is over-expressed on the surfaces of various tumor cells and promotes the cancer cell proliferation, invasion, and metastasis. Nanobodies, characterized by small sizes, high affinities and specificities, and low immunogenicities, are promising diagnostic and therapeutic tools. However, the nanobodies that specific target to CD147 have few reports. In this work, a specific anti-CD147 nanobody have been successful identified using phage display technology. The tumor target and anti-tumor effects have also been detected in different CD147 positive tumors in vitro and in vivo assays, respectively. Meanwhile, it has synergistic effect for inhibiting 4T1 bearing mice through conjugating doxorubicin. It may afford new strategies for cancer therapies.